The clinical and histopathological features of idiopathic inflammatory myopathies with asymmetric muscle involvement. (July 2019) - Liu, Meirong; Hou, Ying; Dai, Tingjun; Lv, Jingwei; Li, Wei; Zhao, Yuying; Fang, Qi; Yan, Chuanzhu
Highlights: 9.2% patients with asymmetric muscle involved were identified in idiopathic inflammatory myopathies. IIMs with asymmetric muscle involvement present highly positive anti-mitochondrial antibodies. The relationship between the presence of AMAs and the asymmetric muscle involvement in DM needs to be further clarified. Abstract: The objective is to determine the frequency of idiopathic inflammatory myopathies (IIMs) with asymmetric muscle involvement (IIMs-A) as initial manifestations in total IIMs and to compare the demographic, clinical, histopathological and radiological characteristics of IIMs-A with classical IIMs (IIMs-C). We retrospectively reviewed the clinical, laboratory, muscle images, histopathological features and treatment response of patients at the Qilu hospital who were diagnosed as IIMs from April 2005 to August 2017. We found among 134 IIMs patients, 13(9.2%) patients with IIMs-A were identified, of which 7 patients were diagnosed as dermatomyositis (DM), 2 as polymyositis (PM), 4 as immune-mediated necrotizing myopathy (IMNM) using the European Neuromuscular Centre (ENMC) criteria. The mean age of our group was 59.1 years old. The duration from the initial symptoms to the first examination was less than 12 months in 12 patients (92.3%). 46.2% patients accompanied with weakness of distal limbs and bulbar symptoms. Finger flexion involvement was found in 5 patients (38.5%). There was no patient that finger flexion was weaker than shoulder abduction. The creatine kinase (CK) level in the serum ranged from 41 IU/L to 9125 IU/L (average: 3192.7 ± 2769.9 IU/L). Serum positive anti-mitochondrial antibodies (AMAs) were found in four patients (30.8%). Endomysial fibrosis and inflammatory cell infiltration were detected in 92.3%, 84.6% patients respectively. Mitochondrial abnormalities in histopathological finding of muscle biopsy were seen in 100% cases. The major histocompatibility complex class I (MHC-I) (84.6%) and class II (MHC-II) (92.3%) expressed on muscle biopsies from almost all cases of our patients. MAC antibody, however, was detected in only 20–40% patients. Eight patients (61.5%) had favorable outcomes. The conclusion was that IIMs-A presented mainly in DM, generally with mitochondrial abnormality and highly positive AMAs. The relationship between the presence of AMAs and the asymmetric muscle involvement in DM needs to be further clarified. We should also consider the diagnosis of IIMs when the patient has features of positive AMAs and asymmetric muscle involvement.